Tingkat Pengetahuan Karang Taruna Cahaya Mandala dalam Pembuatan Kombucha Bunga Kecombrang di Desa Mandalawangi - Eva Kholifah; Deya Adiby Nabillah; Muhamad Suhaemi; Endah Endah; Renditya Ismiyati; Anton Anton; Asep Asep; Balqis Maulana; Surya Ahmaddhani; Syala Nabilah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity was motivated by the potential of local natural resources in the form of Torch Ginger flowers (Etlingera elatior) in Mandalawangi Village, Pandeglang Regency, which have not been optimally utilized despite their high antioxidant activity and potential to be processed into probiotic kombucha beverages that are beneficial for health and possess economic value. The purpose of this activity was to improve the knowledge and skills of members of the Karang Taruna Cahaya Mandala in producing Torch Ginger flower kombucha as an effort to enhance public health and welfare. The activity was carried out through interactive lectures, hands-on training, and counseling using leaflet media, involving 30 respondents selected based on their active participation in the community. Knowledge evaluation was conducted through pretest and posttest assessments using the Wilcoxon test to analyze significant differences in knowledge levels before and after the activity. The results showed an increase in the knowledge level categorized as “good” from 63% before the training to 90% after the training, with a significance value of p = 0.000 (p<0.05), indicating that the activity was effective in improving participants’ understanding of Torch Gingerflower kombucha production. In addition to increasing health awareness, this activity also contributed positively to community economic empowerment through the development of local value-added products. In conclusion, the training and counseling on Torch Ginger flower kombucha production proved effective in enhancing community knowledge and skills; however, further activities are recommended, including business mentoring and product certification, to ensure the sustainability and broader impact of the program.